THE ROLE OF TEACHERS IN BUILDING THE CHARACTER OF THE YOUNG GENERATION - Dwi Aris Nurohman; Sofia Fitri Rahmani; Ahmad Khanali (Adisam Publisher, 2025)
This literature research examines the role of teachers in building the character of the younger generation in the era of globalization. The main focus of this study is to explore various strategies and methods of character education that can be implied by teachers in the learning process. Apart from that, this research also aims to assess the effectiveness of various character learning approaches adopted in various parts of the world. The method used is literature analysis, where data and information are collected from various sources such as academic journals, textbooks and relevant online articles. From this analysis, it was found that teachers play an important role in forming moral values, integrity, cooperation, social awareness, and interpersonal skills, all of which are essential in developing student character. This research identified several effective techniques used by educators, including project-based learning, interactive class discussions, and implementing a fair reward and punishment system. Apart from that, the integration of character values in all aspects of the curriculum and extracurricular activities is also emphasized as an important aspect of character education. In conclusion, teachers act as facilitators and role models in forming the character of the younger generation. This research recommends that educational institutions strengthen professional development programs for teachers, so that they are equipped with relevant skills, knowledge and methods to effectively support student character formation. Further research is recommended to examine the long-term impact of these approaches on student behavior and academic success.